Using Demographic, Socioeconomic and Access Factors to Predict Student Attitudes Toward Computer-Based Learning Technology in a Saudi Nursing Educational Program - Samarkandi, Osama A.; Bashatah, Adel S.; Mobrad, Abdulmajeed; Abdulqader, Nabeel F.; Aljelifey, Raed F.; Alnajada, Asem A.; Alomairy, Abdulaziz A.; Mukhtar, Rasheed (International Journal For Research In Health Sciences And Nursing, 2015)
Computer knowledge and skills are becoming essential components technology in nursing education. Saudi nurses must be prepared to utilize these technologies for the advancement of science and nursing practice in local and global communities. Little attention has been directed to students’ attitudes about computer usage in academic communities in Saudi Arabia. Their attitudes about the use of computers for the enhancement of learning are relatively unknown. Few research studies have been identified that explicate Saudi Arabian nursing students’ attitudes toward computer usage for the acquisition of knowledge and skills. Males and females matriculate at King Saud University (KSU), but attend classes in gender-specific groups. This descriptive correlation study will contribute to the body of